Mengembangkan Bisnis Kopi Berbasis Nilai Ergo-Ikonik: Coffee Business Development Based on Ergo-Iconical Values - Andriyansah Andriyansah; Rulinawaty Rulinawaty; Zulham Adamy; Septiyani Endang Yunitasari; Analisa Svastika Ning Gusti Djajasasmita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The activity of implementing this community service aims to train participants with the target to be achieved is that participants can develop a Coffee Business based on Ergo-Iconical values. The method implemented is the pre-activity stage in the form of an initial meeting through online media, the Coordination Stage, the Implementation Stage, and the Evaluation Stage. Two known methods for maintaining post-harvest coffee quality are dry processing methods and wet methods. Ergo-iconic value is the superiority of market value with the comfort of typical products with dimensions of comfort in the value of function, comfort in the value of usefulness, and comfort in the value of pleasure. The training results also added marketing theories and facts and the application of product marketing strategies in the industrial 5.0 era so that they could develop their coffee business.